(untitled) (Hoboken, N.J., 2007)
This work describes the basic concepts of toxicology and equips readers with the skills required to evaluate risks at given exposures. Topics covered include principles of toxicology, organ toxicology, methods in toxicology, risk assessment and management, and toxicity of chemicals. In addition to toxicology, coverage extends into areas such as the 'omics,' biomarkers, molecular and cell biology, and newer approaches to risk assessment.
Keywords: Toxicology,Poisons,Health risk assessment; Risk assessment